Multiple Argument Marking In Bantoid: From Syntheticity To Analyticity - Hyman, Larry (My University, 2017)
This paper addresses the mechanisms of change that lead from syntheticity to analyticity in the Bantoid languages of the Nigeria-Cameroon borderland area. I address the different strategies that are adopted as these languages lose applicative “verb extensions” found elsewhere in Bantu and Niger-Congo. I show that although historical recipient, benefactive, and instrumental applicative marking on verbs allowed multiple object noun phrases (send-APPL chief letter, cook-APPL child rice, cut-APPL knife meat), they have been replaced by adpositional phrases and/or serial verb constructions in all branches of Bantoid. I map out the different analytic strategies that have been adopted and reconstruct the original verbal, nominal and pronominal sources of the different grammaticalization processes. Of particular interest is the development of a recipient/benefactive preposition ‘to, for’ from the word for ‘hand’ and a comitative/instrumental preposition ‘with’ from a third person plural pronoun.
Keywords: Bantoid; syntheticity; analyticity